A Survey on Congenital Head Malformations in Calves - Esam Mosbah; Walaa F. Awadin; Marwa Abbas (Journal of Applied Veterinary Sciences, 2022)
Congenital malformations are structural and functional abnormalities that present at birth. Congenital head malformations were present in 231 (22 bovine and 209 buffalo) calves referred to Mansoura veterinary teaching hospital, beside private farm stations at Dakahleya Province, and during field training trips between October 2015 and December 2021. This survey was carried on for the awareness of scientists, veterinarians and animals' owners. Diagnosis of those abnormalities was based on history and clinical examinations that were dependent upon visual inspection and surgical exploration. Those head malformations include: anophthalmia (0.43%), enophthalmos (0.43%), unilateral and bilateral strabismus (squint) (1.72%), heterochromia iridis (86.58%), conjunctival dermoid cyst (0.86%), cheiloschisis (harelip) (0.43%), campylognathia (curved jaw) (3%), absence of external ear (anotia) (0.43%), nasal dermoid (0.43%), double tongue (0.86%), hydrocephalus (0.86%), diprosopus (double face) (0.86%), cranioschisis (0.86%), cyclopia (0.43%). Buffalo calves were found with more congenital head malformations than bovine calves. In bovine, mixed breed calves have higher incidence of head malformations compared to native. Surgical treatment was carried out for cases affected with conjunctival dermoid cyst, nasal dermoid, double tongue, cranioschisis. Congenital anomalies which cannot be corrected surgically but the animal will survive in a normal condition were: campylognathia (curved jaw), strabismus, heterochromis iridis and anotia.